Mechanical behaviour of polymer based bamboo composite 2 - Jamil, Zulkeple (2016)
Composite is a combination of two or more constituent materials, when two materials with a different properties were combined, it produces a material which has superior properties than a single material. Natural fibers can be defined as a fiber that produces by a plant or animal, which is categorized as a renewable resource. Natural fibers are commonly used as a reinforced such as hemp, jute, kenaf, and sisal. Mostly, they contribute in a lot of sectors such as an automobile, furniture, packing construction and sport. This experiment used thermoplastic (Polypropylene) as matrix and natural bamboo from a “Gigantochloa Levis” species as the fiber of the composite. The first objective of this project is to design and fabricate a bamboo composite specimen by using a Polypropylene as a matrix. The second objective is to investigate the tensile and impact properties of the composite and lastly to characterize the bamboo specimen after fracture. Firstly, the process to extract the fiber from the raw bamboo is to separate the fiber from the raw bamboo culm. There are various extraction techniques, and for this experiment, mechanical extraction technique was implemented by using the Hammer Mill machine. Based on this technique, the raw bamboo was cut into a long strip before were put into the machine, and then the bamboo strip will be grinded to produce a bundle of fiber. After a bundle of fiber extracted, the next process is to mix up the matrix and reinforcement material. This mixing process is very crucial to ensure that the composites have a good bonding. For the mixing process, composite mixed into three different compositions which are 20% BF + 80 % PP, 30 % BF + 70 % PP and 40% BF + 60% PP by using Internal Brabender Mixer machine. After that, Hot Press & Cold Press technique was used to form a composite. This technique started with installing a mixed composite into a mold, and then the mold will be transferred to the hot press section. Next, the hot mold was moved to the cold press section for the curing process. This process repeated for three different compositions as mentioned before. By using this fabricating technique, the composite was formed with a dimension of 3mm x 150mm x 150mm sheet shape. Finishing process was required to obtain the desired specimen by referring to the ASTM D638 for Tensile Test and ASTM D256 standard for the impact test. Finally, the composite was cut manually by using Vertical Band saw machine to get the requirement shape specimen for Izod Impact Test and Tensile Test. For the prepared specimens, Impact Test and Tensile Test were conducted by using INSTRON 3369 test machine and CEAST 9050 test machine, respectively. In order to characterize the bamboo specimen, the broken specimens from the tests were collected and the characteristics of the composition are observed under Video Measuring System Machine. As a conclusion, based on the collected result, the increment of the bamboo fiber composition into the composite lead to lower tensile and impact properties. This occured because the interfacial bonding of composite became weak due to less amount of bonding agent. In this experiment, the one and only bonding agent for the composite is polypropylene. Thus, when the composition of polypropylene reduces, bonding agent of composite minimize. As a consequence, the interfacial bonding of composite became weak and easily to fail when force is applied.